A New Algorithm For Reconstruction Of A Computer-Generated Hologram (CGH). (10th December 2020) - Tripathy, A K; Tripathy, S K; Pattanaik, S R; Das, S K
Abstract: A new algorithm based on cell orientation for construction of detour Fourier Transform Computer Generated Hologram (CGH) and reconstruction of original objects from the CGH is presented here. Uniqueness of this investigation is that, besides reconstructing original objects, using this proposed algorithm, these can also be reconstructed without using monochromatic light. This investigation thus finds its importance in encryption applications. The proposed algorithms are faster as compared to Elliptic Curve Cryptography (ECC) algorithm and consumes less power.